Economic geographies : circuits, flows and spaces - Hudson, Ray, 1948- (SAGE, 2005)
How do we conceptualise the production and re-production of social life? What are the most appropriate ways to conceptualise capitalist economies and their geographies? Economic Geographies integrates ideas of structure, agency, and practice to provide: A detailed overview of recent key debates in economic geography: from political-economy and Marxism to post-structuralism A explanation of the of relations between production, retail and consumption, governance and regulation A discussion of the economy in terms of circuits, flows, and spaces that systematically relates the material to the cult.